Besnoitia besnoiti and Toxoplasma gondii: two apicomplexan strategies to manipulate the host cell centrosome and Golgi apparatus - Cardoso, Rita (2015)
Besnoitia besnoiti and Toxoplasma gondii are two closely related parasites that interact with the host cell microtubule cytoskeleton during host cell invasion. Here we studied the relationship between the ability of these parasites to invade and to recruit the host cell centrosome and the Golgi apparatus. We observed that T. gondii recruits the host cell centrosome towards the parasitophorous vacuole (PV), whereas B. besnoiti does not. Notably, both parasites recruit the host Golgi apparatus to the PV but its organization is affected in different ways. We also investigated the impact of depleting and over-expressing the host centrosomal protein TBCCD1, involved in centrosome positioning and Golgi apparatus integrity, on the ability of these parasites to invade and replicate. Toxoplasma gondii replication rate decreases in cells over-expressing TBCCD1 but not in TBCCD1-depleted cells; while for B. besnoiti no differences were found. However, B. besnoiti promotes a reorganization of the Golgi ribbon previously fragmented by TBCCD1 depletion. These results suggest that successful establishment of PVs in the host cell requires modulation of the Golgi apparatus which probably involves modifications in microtubule cytoskeleton organization and dynamics. These differences in how T. gondii and B. besnoiti interact with their host cells may indicate different evolutionary paths.